Enseigner en intégrant l’urgence climatique : propos d’enseignant·es en formation - Kristine Balslev; Lora Naef (Éducation et Socialisation)
Faced with the challenges of global warming, which are likely to have a major impact on the generation currently in school, the role of schools is being questioned by climate activist teachers. We describe a research and training project aimed at teachers who wish to develop and share how they integrate the climate emergency into their practice, and analyse the discourses produced in this context. A number of key themes emerge from this analysis, particularly in terms of concerns and projected courses of action. Teachers’ comments are discussed in the light of ways in which environment and ecology have been treated as a school subject since the 1970s. The results highlight the diversity and richness of the activities proposed and the strong commitment of these teachers to integrate the climate emergency into their practice. They also highlight the paradoxical role of pupils, who can both motivate and hinder this commitment.